Pressure Management in Water Distribution Networks by Means of Pumps as Turbines: A Case Study in Northern Italy - Lucrezia Manservigi; Valentina Marsili; Filippo Mazzoni; Giulia Anna Maria Castorino; Saverio Farsoni; Enzo Losi; Stefano Alvisi; Marcello Bonfè; Marco Franchini; Pier Ruggero Spina; Mauro Venturini (Engineering proceedings, 2024)
Pressure control by means of pressure-reducing valves (PRVs) is a possible strategy to reduce water losses in water distribution networks (WDNs). However, PRV replacement with energy-harvesting devices—such as pumps as turbines (PATs)—can lead to a more sustainable management of water systems. This study analyzes the case study of a WDN located in Northern Italy, of which the layout is supposed to be upgraded by installing a PAT for both pressure reduction and energy recovery. To identify the optimal PAT to install (i.e., the one that maximizes energy recovery), a fleet of forty-five turbomachines is hypothetically employed. The study reveals that the hydraulic regulation of the optimal PAT allows recovering over 50% of the hydraulic energy available in the WDN.